Mechanistic study of the effect of a high-salt diet on the intestinal barrier - Li Chen; Junrui Tang; Yanglin Xia; Jie Wang; Li-na Xia (Scientific Reports)
Abstract Despite the established link between chronic high salt diet (HSD) and an increase in gut inflammation, the effect of HSD on the integrity of the intestinal barrier remains understudied. The present study aims to investigate the impact of HSD on the intestinal barrier in rats, encompassing its mechanical, mucous, and immune components. Expression levels of intestinal tight junction proteins and mucin-2 (MUC2) in SD rats were analyzed using immunofluorescence. The expression area of goblet cell mucopolysaccharides was assessed through PAS staining. Additionally, serum D-lactic acid, SIgA, β-defensin, and colonic tissue cytokines were measured using ELISA. Rats fed with HSD exhibited decreased expression of tight junction proteins, particularly Occludin, resulting in impairment of the intestinal epithelial barrier and an elevated serum D-lactic acid level. Furthermore, a notable reduction in the expression of goblet cell mucopolysaccharides, along with lower β-defensin and MUC2 levels, was observed. Notably, the SIgA and immune-related cytokines were significantly reduced in the HSD group. HSD disrupts the intestinal barrier in rats, leading to increased permeability and the entry of inflammatory factors into the bloodstream. This finding suggests that HSD may contribute to the pathogenesis of various diseases.